2012
DOI: 10.1021/jf3010367
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Directed Isolation and Identification of Phytotoxic and Fungitoxic Acetylenes from Conyza canadensis

Abstract: Conyza canadensis (L.) Cronquist syn. (horseweed) is a problematic and invasive weed with reported allelopathic properties. To identify the phytotoxic constituents of the aerial parts, a systematic bioactivity-guided fractionation of the dichloromethane extract was performed. Three active enyne derivatives, (2Z,8Z)-matricaria acid methyl ester, (4Z,8Z)-matricaria lactone, and (4Z)-lachnophyllum lactone, were identified. The lactones inhibited growth of the monocot Agrostis stolonifera (bentgrass) and the dicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
3
31
1
1
Order By: Relevance
“…Compound 3 was also detected in both fractions, but in very small quantities, rendering its isolation impossible. The low concentrations of compound 3 in the extracts differed from the earlier findings of Queiroz et al, 7 who isolated it in larger amounts from North American specimens. This was not unexpected, because the composition of C. canadensis essential oil can vary according to the collection site and the growth phase of the plant.…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…Compound 3 was also detected in both fractions, but in very small quantities, rendering its isolation impossible. The low concentrations of compound 3 in the extracts differed from the earlier findings of Queiroz et al, 7 who isolated it in larger amounts from North American specimens. This was not unexpected, because the composition of C. canadensis essential oil can vary according to the collection site and the growth phase of the plant.…”
Section: Resultscontrasting
confidence: 92%
“…In a first trial, C. canadensis specimens collected in Brazil were extracted using dichloromethane, chloroform, and hexane, as described by Queiroz et al,7 in order to determine whether the compounds isolated from North American specimens were also present in specimens growing in Brazil. Using GC-MS analysis, it was possible to confirm that compounds 1 and 2 were present in both hexanic and chloroformic fractions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About antifungal mechanisms, it was reported that the compound 22 is a fungal endo-β-(1,3)-glucanase inhibitor (Vargas-Arispuru et al, 2009). Others active compounds (Figure 1) are acetylenic lactone (27) (Queiroz et al, 2012), 2-phenylethanol ester (28) (Labbé et , 2005), and the unusual 2-hydroxy-1-H-phenalen-one (29) and 2-methoxy-1-H-phenalen-one, which are fungicides against Colletotrichum, Cladosporium, and Mycosphaerella, respectively (Otálvaro et al, 2007). Other compound also toxic to Colletotrichum was the known glucosinolate glucoraphanin, isolated from Brassica oleracea (Lara-Viveros et al, 2014) Plants are able to produce proteinaceous compounds, between those described with fungicide activity are lectins (glycoproteins that agglutinate and immobilize microorganisms) and microbial proteinase inhibitors (inhibit enzymes that degrade plant cell walls).…”
Section: Gaeumannomyces Graminismentioning
confidence: 99%